The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1103/physrevfluids.1.054403
|View full text |Cite|
|
Sign up to set email alerts
|

Cascades and spectra of a turbulent spinodal decomposition in two-dimensional symmetric binary liquid mixtures

Abstract: We study the fundamental physics of cascades and spectra in two-dimensional (2D) Cahn-Hilliard-Navier-Stokes (CHNS) turbulence, and compare and contrast this system with 2D magnetohydrodynamic (MHD) turbulence. The important similarities include basic equations, ideal quadratic invariants, cascades, and the role of linear elastic waves. Surface tension induces elasticity, and the balance between surface tension energy and turbulent kinetic energy determines a length scale (Hinze scale) of the system. The Hinze… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…For the binary mixture plots we also overlay the iso-contour of the order parameter φ for φ = 0 to highlight the interface. size of binary-fluid domains lie within the inertial range (Aronovitz and Nelson 1984;Perlekar et al 2014;Fan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For the binary mixture plots we also overlay the iso-contour of the order parameter φ for φ = 0 to highlight the interface. size of binary-fluid domains lie within the inertial range (Aronovitz and Nelson 1984;Perlekar et al 2014;Fan et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The definition of the typical blob size varies from one study to the next. Since this measure is also commonly used in the study of phase separation through spinodal decomposition (Fan et al, 2016), we chose here to use the same definition (see Methods). This allowed us to directly compare our dynamics to a purely physical situation.…”
Section: Dynamics Of Cell Sorting In Hydra Aggregatesmentioning
confidence: 99%
“…In our previous study [9], we stressed the analogy between 2D CHNS and 2D MHD. The energy in MHD consists of two parts: kinetic energy and magnetic energy.…”
Section: Fig 5: the Time Evolution Of Elastic Energy (Run2)mentioning
confidence: 98%
“…The two systems have identical ideal quadratic conserved quantities, and they both exhibit dual cascades. Our previous work [9] showed that the mean square concentration spectrum for the 2D CHNS system in the elastic range is ∼ k −7/3 , and it is associated with an inverse cascade of mean square concentration. Note that the power −7/3 is the same as the power for the mean square magnetic potential spectrum in 2D MHD.…”
mentioning
confidence: 95%